ANALISIS CAPM DAN FFTFM TERHADAP EXCESS RETURN SAHAM PERBANKAN DI INDONESIA - Debora Gloria Serepina,; Tri Siswantini, (2022)
This research was conducted to analysis and test the asset valuation model on excess return of general banking stocks listed on the Indonesia Stock Exchange from 2016 to 2020. The sampling technique used in this study is the purposive sampling method. Based on the criteria of the predetermined sample, a total of 40 banking companies was obtained. Data analysis in this study was carried out using Microsoft Office Excel 2010, and the hypothesis test using SPSS program version 25.0. In this research, the researcher analyzed each model in calculating excess returns and tested models with linear regression test, simultaneous test and coefficient of determination test. The results of this study indicate that both asset valuation models have an effect on the excess returns of banking stocks. The CAPM model succeeded in determining 16 efficient stocks and the FFTFM model succeeded in detrmining 1 efficient portofolio with an excess return value of 0.39% and 3 optimal portfolios with an excess return value of 3.94%, 1.27% and 1.56%